2018
DOI: 10.18410/jebmh/2018/332
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Breech Presentation and Maternal and Perinatal Outcome in a Tertiary Care Hospital of Western Rajasthan

Abstract: BACKGROUNDBy definition breech presentation means foetal buttocks or the podalic pole of foetus is the presenting part, with sacrum being the denominator. Most newborns are born with cephalic presentation, but at the end of pregnancy around 2.5%-3% are found to be breech Before the end of pregnancy, the breech presentation is much more common about 20% of babies at 28 weeks are breech and 15% at 32 weeks. Caesarean section for breech presentation has been suggested as a way of reducing the associated perinatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…13,15 Rana et al in their study showed that primi breech was the commonest indication for caesarean section (54.32%) followed by post caesarean section breech (14.81%) and bad obstetric history (9.8%). 10 Further, other indication for caesarean section were FPD 1.2%, foetal distress 7.4%, PIH 4.93% and placenta previa 7.4%. This study conducted in small populations.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…13,15 Rana et al in their study showed that primi breech was the commonest indication for caesarean section (54.32%) followed by post caesarean section breech (14.81%) and bad obstetric history (9.8%). 10 Further, other indication for caesarean section were FPD 1.2%, foetal distress 7.4%, PIH 4.93% and placenta previa 7.4%. This study conducted in small populations.…”
Section: Discussionmentioning
confidence: 87%
“…Rana et al in their study reported that breech presentation was most common in 21-25 years age-group (44.76%) followed by 16-20 years (26.74%). 10 Similarly, Choudhary et al reported maximum breech (70.6%) in age-group 20-30 years. 11 In the present study, approximately 64.4% were primigravida and 35.6% were multigravida.…”
Section: Discussionmentioning
confidence: 87%
“…Prematurity (28.48%) was reported as the commonest cause of breech in the study by Bhati RS, Choudhary SI. 3 The other causes were multiple gestation (6.83%), IUGR (4.80%), grand multiparity 4.07%, oligohydramnios (3.88%), anomalies of uterus (3.51%), polyhydramnios (2.40%), contracted pelvis (2.77%), placenta previa (1.66%), hydrocephalus (1.48%). In this study, the maximum number of the breech presentation delivered vaginally.…”
Section: Discussionmentioning
confidence: 99%